Evidence-based management of COVID-19 in cancer patients: Guideline by the Infectious Diseases Working Party (AGIHO) of the German Society for Haematology and Medical Oncology (DGHO). (November 2020) - Giesen, Nicola; Sprute, Rosanne; Rüthrich, Maria; Khodamoradi, Yascha; Mellinghoff, Sibylle C.; Beutel, Gernot; Lueck, Catherina; Koldehoff, Michael; Hentrich, Marcus; Sandherr, Michael; von Bergwelt-Baildon, Michael; Wolf, Hans-Heinrich; et al.
Abstract: Since its first detection in China in late 2019 the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the associated infectious disease COVID-19 continue to have a major impact on global healthcare and clinical practice. Cancer patients, in particular those with haematological malignancies, seem to be at an increased risk for a severe course of infection. Deliberations to avoid or defer potentially immunosuppressive therapies in these patients need to be balanced against the overarching goal of providing optimal antineoplastic treatment. This poses a unique challenge to treating physicians. This guideline provides evidence-based recommendations regarding prevention, diagnostics and treatment of SARS-CoV-2 infection and COVID-19 as well as strategies towards safe antineoplastic care during the COVID-19 pandemic. It was prepared by the Infectious Diseases Working Party (AGIHO) of the German Society for Haematology and Medical Oncology (DGHO) by critically reviewing the currently available data on SARS-CoV-2 and COVID-19 in cancer patients applying evidence-based medicine criteria. Highlights: Cancer patients are vulnerable to severe acute respiratory syndrome coronavirus 2 infection and severe COVID-19. Comprehensive management strategies are required in care for cancer patients. Evidence-based recommendations help clinicians make informed treatment decisions. Providing state-of-the-art cancer care is possible during COVID-19 pandemic.